Mechanical performance and shape memory behavior of 4D printing polylactic acid/biobased thermoplastic polyurethane - Mohd Nazeri, F. N.; Jalil, H. A. A.; Anuar, Hazleen; Manshor, M. R. (Universiti Teknikal Malaysia Melaka (UTeM), 2025)
Shape memory materials (SMMs) possess the unique ability to return to their original shape after deformation when exposed to external stimuli, making them highly desirable for applications such as biomedical devices and smart textiles. This study investigates the enhancement of polylactic acid (PLA) by incorporating bio-based thermoplastic polyurethane (bTPU) to improve flexibility and shape recovery. PLA/bTPU blends were prepared at varying weight ratios and characterized for mechanical properties, morphology, and shape memory behavior. Results showed that elongation at break increased dramatically from 7.66% in neat PLA to 944.14% in PLA60, indicating a substantial improvement in ductility. Although tensile strength decreased from 43.26MPa (PLA) to 21.80MPa (PLA60), this trade-off was balanced by enhanced flexibility. Morphological analysis revealed a transition from brittle fracture in PLA to ductile, phase-separated “sea-island” morphology in PLA60, with continuous bTPU domains promoting energy dissipation. FTIR analysis confirmed the presence of functional groups associated with PLA and bTPU without new peak formation, indicating physical blending rather than chemical interaction. Shape recovery tests revealed that recovery improved from 48.25% in PLA to 81.48% in PLA60 under thermal stimulation at 85°C. These results suggest that PLA/bTPU blends offer improved mechanical resilience, elasticity, and shape memory behavior, making them suitable for sustainable 3D and 4D printing applications in fields requiring adaptable material performance. This research contributes to sustainable material engineering and supports the development of adaptable materials for aerospace, automotive, and bioengineering applications